Evidence for Griffiths phase in multiferroic BiMnO₃ and BiFe₀.₅Mn₀.₅O₃ films - Prokhorov, V.G.; Kaminsky, G.G.; Kim, J.M.; Yoо, Y.J.; Lee, Y.P.; Svetchnikov, V.L.; Levchenko, G.G.; Nikolaenko, Yu.M.; Khokhlov, V.A. (Физика низких температур, 2012)
Microstructure and magnetic properties of the BiMnO₃ and BiFe₀.₅Mn₀.₅O₃ films, prepared by the rf magnetron
sputtering on LaAlO₃ (001) single-crystalline substrate, have been investigated. The selected-area electron
diffraction analysis allows us to indentify the crystal structure of the BiMnO₃ film as an orthorhombic one while
the BiFe₀.₅Mn₀.₅O₃ film has a hexagonal lattice symmetry. The high-resolution electron microscopy study reveals
the presence of strip-domain phase with a periodic spacing of about 3c in both films. The magnetic measurements
show that in addition to the basic paramagnetic phase, the films manifest the Griffiths phase behavior
in a wide temperature range. We argue that the observed weak ferromagnetism is provided by an appearance of
the strip-domain layered inclusions rather than the intrinsic physical origin of the films.